2021
DOI: 10.1016/j.ssresearch.2021.102596
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of trustworthiness in cross-status interactions

Abstract: Although the literature on trust is vast, little is known about the attributes that trigger or inhibit trusting others we do not know. Using a vignette version of the trust game, we addressed the role that social standing plays in estimating trustworthiness of strangers in cross-status interactions in Chile, a non-WEIRD context also characterized by high inequality and social segregation. We found no relationship between the socioeconomic status of trustors and trusting behavior. However, trustees' income was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…I.e., target social status could influence prosociality more than individual social status. Previous research, in both WEIRD (Navarro-Carrillo et al, 2018;Van Doesum et al, 2017) and non-WEIRD societies (Salgado et al, 2021) has shown that individuals behave less prosocially toward higher status than lower status targets.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…I.e., target social status could influence prosociality more than individual social status. Previous research, in both WEIRD (Navarro-Carrillo et al, 2018;Van Doesum et al, 2017) and non-WEIRD societies (Salgado et al, 2021) has shown that individuals behave less prosocially toward higher status than lower status targets.…”
Section: Discussionmentioning
confidence: 94%
“…This ambivalence could be explained because reliance on others might be an adaptive strategy for lower-status individuals, but it also offers "enhanced opportunity for malfeasance" (Granovetter, 1985, p. 491). Investing in unreliable relationships can be very costly for those who have less (Fiske et al, 2012;Salgado et al, 2021). Since individuals from disadvantaged backgrounds are more negatively affected by unfavorable treatment in social exchanges, they are expected to have heightened vigilance to external threats and more hostile reactivity when facing exploitative behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Or is it the person of lower status who may be perceived as less greedy, more empathic, and more willing to reciprocate to arrive at a mutually beneficial outcome 21 , 32 , 33 ? More specifically, although social status fundamentally shapes how we think, feel, and behave towards others 6 , it remains unclear how trust is conferred within hierarchies based on socioeconomic status (SES, hereafter referred to as “status”) 34 37 and what cues we use to infer status when trusting others with our resources. In the present research, we fill this gap in knowledge, by examining how ascribed (i.e., conveyed via cues paired with status knowledge) and perceived (i.e., inferred from visual cues) SES of individuals who are either high or low in this status dimension impacts financial investments during a resource sharing task called the Trust Game 38 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Trust, in particular, builds on an innate orientation towards others, rooted in social preferences such as altruism or generosity and a component of calculated risk-taking, which Torbiörn (2002) defines as "the willingness to be vulnerable" that reflects the expectation of trustworthiness or reciprocation by others. While altruism is a personal trait, "expectation of trustworthiness" (Barr, 2003;Ashraf et al, 2006;Salgado et al, 2021) is built through experience in a social network (see Granovetter, 1985). Tullberg (2008) distinguishes between personal traits versus experience as main drives of trust and claims that trust increases with the degree of perceived trustworthiness in society.…”
Section: Introductionmentioning
confidence: 99%